Spirometryin Smokers and Non-smokers: A Comparative Study - Shrestha, Lava; Mahotra, Narayan Bahadur; Rana, Binaya Shumsher Jung Bahadur; Banstola, Dinesh; Amatya, Tara Man; Mahat, Barun (Journal of Karnali Academy of Health Sciences, 2019)
Introduction : Spirometry is the process of recording volume of air that moves into and out of the lungs. It is a physiological test that measures how an individual breathes air volumes as a function of time. It provides an objective and quantitative measure of lung function. Smoking produces increase in epithelial damage, cellular inflammatory infiltrates, muscles and fibrosis in respiratory airways and is responsible for acute respiratory illnesses including pneumonia, impaired lung growth, early onset decline in lung function, poor asthma control, chronic obstructive pulmonary disease (COPD). Early identification of reduction in lung function of smokers by spirometry can be very important in order to encourage them to stop smoking. Methods: This study included a total of 106 individuals, 51 were smokers and55 were non-smokers. The participants performed spirometry in the sitting position by open circuit method. Parameters of spirometry FVC, FEV1, FEV1/FVC and PEFR were recorded collected in the form of percentage of predicted. Results: The mean FVC in smokers and non-smokers were 99.98±9.88% and 102.97±8.03% respectively (p=0.092). The mean FEV1 in smokers and non-smokers were 99.65±9.61% and 104.58±10.03% respectively (p=0.011). The mean FEV1/FVC ratio in smokers and non-smokers were 103.25±4.60% and 105.57±5.10% respectively (p=0.016). The mean PEFR in smokers and non-smokers were 102.11±8.40% and 106.01±10.62% respectively (p=0.038). Conclusion: The spirometry parameters of pulmonary function were better in non-smoker group. Spirometry can be useful in detecting reduction in pulmonary function before appearance of any symptoms or before pulmonary functions become significantly abnormal.